Long-term growth and policy challenges in the large emerging economies - Conway, Paul (OECD Publishing, 2010)
Taken together, Brazil, China, India, Indonesia and South Africa - the "BIICS" - have been an important engine for world growth, and they account for a growing share of global output. However, further reforms will be needed to ensure catch-up to OECD GDP per capita levels over the long term. This paper uses the OECD's Going for Growth framework, as well as other available evidence linking policies to economic performance, to identify key structural policy challenges in the BIICS for the years ahead. While such challenges vary from country to country, common areas for reform include strengthening policies in the areas of education, product market regulation and labour markets, as well as improving more basic market institutions. This Working Paper relates to the OECD's Economic Policy Reforms: Going for Growth 2010 (www.oecd.org/goingforgrowth) and the Economic Surveys of China, India, South Africa, Indonesia, and Brazil (www.oecd.org/eco/surveys)
Keywords: Economics